Influence of TiO2 dispersion on silica support toward enhanced amine assisted CO2 photoconversion to methanol. (April 2022) - Khusnun, N.F.; Jalil, A.A.; Abdullah, T.A.T.; Latip, S.S.M.; Hitam, C.N.C.; Fauzi, A.A.; Hassan, N.S.; Aziz, M.A.H.; Rahman, A.F.A.; Aziz, F.F.A.; Bahari, M.; Adnan, R.H.; et al.
Abstract: In this work, titania-supported fibrous silica (TiO2 -KCC1) and Fibrous Silica-Titania (FST) were prepared via microemulsion technique with a different sequence of titania incorporation method. The catalysts were characterized by x-ray diffraction (XRD), N2 adsorption-desorption, field emission scanning electron microscopy (FESEM), transmission electron microscopes (TEM), and fourier-transform infrared spectroscopy (FTIR). The results discovered that the FST catalyst had high crystallinity, higher specific surface area, and large pore volume. The alternate arrangement of TiO2 and silica in the framework of fibrous silica on FST catalyst had an excellent dispersion and it triggered stronger TiO2 –SiO2 interactions. It was observed that in the absence of triethylamine (TEA), formic acid (HCOOH) was much favourable produced by both catalysts, with the highest HCOOH product was obtained using TiO2 /KCC-1 (2933 µmol/gcat .h). In the presence of TEA as a sacrificial agent, superior methanol production was perceived using FST (3487 µmol/gcat .h) as compared to TiO2 /KCC-1 (2773 µmol/gcat .h). It was proposed that the unique structure of the FST catalyst absorbed many photons and was able to absorb more carbon dioxide (CO2 ) molecules onto the active site of the catalyst to produce carbonic acid (H2 CO3 ) active radicals. With the assist of TEA, methanol production drastically boosts up almost three times higher than the absence of TEA, probably due to an excess of electrons leading to the formation of more active radicals, thus enhancing the methanol production. The response surface methodology (RSM) result indicated that the utmost yield could be obtained at catalyst dosage 0.619 g/L, TEA volume 157.24 µL, and CO2 flow rate 9.47 mL/min. The experimental validation of the predicted optimum condition revealed that the methanol yield is 3062.966 mol g −1 h −1, compared to the predicted value of 3026.95 mol g −1 h −1, with only a 1.18% difference. Graphical Abstract: ga1 Highlights: The high dispersion of TiO2 in FST had brought an excellent methanol production. The alternate arrangement of TiO2 -SiO2 in FST triggered a stronger interaction. Only formic acid was produced in the absence of TEA. The presence of TEA drastically boosted-up the methanol yield by three times. Energy level of FST was sufficient to produce methanol directly from H2 CO3 species.